Progress towards universal HIV testing among TB patients in Viet Nam: a retrospective cohort evaluation of TB/HIV surveillance, 2011-2017 - Nguyen Binh Hoa; Nguyen Viet Nhung (BMC, 2019)
Abstract Background Tuberculosis (TB) and HIV remain a major causes of morbidity and mortality globally. We conducted an analysis of TB/HIV surveillance data to describe the trends in HIV testing coverage and HIV positivity rate among TB patients in Viet Nam, 2011-2017. Main text This was a descriptive study based on review and analysis of surveillance data from the National Tuberculosis Control Programme from 2011 to 2017. During this period, 721 342 TB cases were diagnosed. Of these, 520 490 (72.2%) had a previously documented HIV status or were tested for HIV during TB care and treatment. The proportion of TB patients whose HIV status was reported increased, from 58.5% in 2011 to 82.9% in 2017 (P value for trend = 0.014). The proportion of TB patients infected with HIV decreased, from 8.0% in 2011 to 3.7% in 2017 (P value for trend = 0.018). Conclusions The proportion of TB patients with a reported HIV status was increased from 2011 to 2017, however HIV testing coverage remained below the National Tuberculosis Control Programme targets (≥ 90%). National Tuberculosis Control Programme needs to focus on ensuring every registered TB patients has a documented HIV status, ensuring full coverage of HIV testing as part of routine TB care.